Two microporous Fe-based MOFs with multiple active sites for selective gas adsorption. Issue 15 (8th February 2017) - Li, Yun-Wu; Yan, Hui; Hu, Tong-Liang; Ma, Hui-Yan; Li, Da-Cheng; Wang, Su-Na; Yao, Qing-Xia; Dou, Jian-Min; Xu, Jian; Bu, Xian-He
Abstract : Two Fe-based porous MOFs have been constructed from dimeric Fe-clusters and rod-shaped heterobimetallic Fe/Na-chains as SBUs, respectively. Notably, both of them exhibit highly selective CO2 uptake over CH4 and N2 owing to abundant multiple active sites. Abstract : Two Fe-based porous MOFs have been constructed from dimeric Fe-clusters and rod-shaped heterobimetallic Fe2 Na3 n chains as SBUs, respectively. Both of them exhibit highly selective CO2 adsorption over CH4 and N2, owing to their abundant multiple active sites.